Management of mite infestation in capsicum - Bharti, Hemlata; Mishra, Ajay Kumar; Nandimandalam, Hemalatha (Indian Horticulture, 2025)
Capsicum is an annual or biennial crop having high nutritional value and consumers appreciate fruits for variable size, colour, flavour, and texture. Due to significant economic potential for marginal and small farmers, and hi-technology intervention, production of capsicum has increased considerably in recent years in almost every part of the country from plains to hills and in open field conditions to different types of protected structures. But capsicum is highly threatened by pests mainly mites, in all phases of their lifecycle with an annual loss of up to 40-100%. These are the important pests which limits capsicum cultivation causing low yield and economic loss in net houses and polyhouses and in open fields. This article mainly discusses the life cycle, infestation, symptoms of mites and their management practices.